Development of therapy aids with electromyography technology for post-stroke patients - Savitri Citra Budi; Budi Sumanto; Lilik Dwi Setyana; Prima Asmara Sejati; Siti Alimah (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: The prevalence of stroke in Indonesia has been increasing and has had a significant impact on individuals, families, and society. There is a pressing need for innovative assistive devices that support independent therapy and enhance patient motivation to improve post-stroke productivity. This study aimed to design and develop a post-stroke rehabilitation assistive device utilizing electromyography (EMG) technology. Methods: This study employed a research and development (R&D) design. Data were collected through documentation studies, interviews with physiotherapists, observations, and focus group discussions (FGDs). A documentation study was conducted using the medical records of stroke patients. Interviews were conducted with physiotherapists, and observations were carried out to understand patients’ therapeutic activities. Results: This study provided alternative therapy by developing post-stroke rehabilitation aids with EMG technology. Based on the documentation study, 88% of patients experienced ischemic stroke with a good level of consciousness (E4V5M6), indicated by the Glasgow Coma Scale (GCS) score of 15. Conclusion: This phenomenon supported the development of electrical therapy innovations to accelerate stroke recovery. This study successfully designed a hand therapy device using EMG technology to improve patients’ motor function, particularly among those with E4V5M6 levels of consciousness and limited motor skills.